Pemberian Terapi Oralit Pada Pasien Anak Dengan Diare dan Pencegahan Dehidrasi Ringan di Wilayah Karang Klesem - Darsiti D; Priyatin Sulistiyowati; Dwi Astuti (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Background: Diarrhea is the main cause of malnutrition in toddlers. Diarrhea in children can lead to nursing problems, nutritional imbalances, skin integrity, causing discomfort or pain, hyperthermia, hypokalemia and until the most common problem is fluid volume deficiency, giving ORS to children with diarrhea can prevent dehydration. The WHO recommended ORS not only restores the balance of sodium and potassium concentrations, but also accelerates the healing of diarrhea compared to the old ORS so that its use is recommended in patients with acute diarrhea with mild-moderate dehydration. Purpose: Describe the administration of ORS therapy to pediatric patients with diarrhea and prevention of dehydration in the Karang Klesem area. Methods: This study used a case study method with children with diarrhea as respondents. Using 3 instruments, namely observation sheets, interview sheets and the Gordon assessment format. This research was conducted in Karangklesem Village for 3 days. Results: After 3 days of action, the child's diarrhea improved. Conclusion : . ORS can prevent dehydration in children with diarrhea problems.